Fungal Infections: Their Diagnosis and Treatment in Transplant Recipients - David H. Van Thiel; Magdalena George; Christopher M. Moore (International Journal of Hepatology)
Systemic fungal infections typically occur in individuals who are seriously ill with recognized risk factors such as those frequently found in transplant recipients. Unfortunately, they are often diagnosed late, when the efficacy of the available treatments is low, often less than 50%, and the cost in terms of lives lost, hospital length of stay, and total hospital costs is substantially increased. The application of antifungal therapies associated with reported efficacy rates greater than 50% are those used prophylactically. When used prophylactically, these infections are reduced in greater than 95% of the expected cases. The choice of a prophylactic agent should be based upon its ease of administration, lack of adverse effects, reduced likelihood of potential drug interactions, and its efficacy in patients with established risk factors and comorbid disease processes that include renal, hepatic, and chronic pulmonary disease. The indications for the use of currently available antifungal agents, their adverse effects, drug interactions, ease of dosing, and applicability in patients with preexisting disease states, and especially in liver transplant recipients, are presented in this paper.